2015
DOI: 10.1007/s00107-015-0879-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing mechanical properties of particleboards using plasma treated wood particles

Abstract: The surface properties of wood particles are one of the key factors for the development of mechanical and physical properties of particleboards. Particles were treated with plasma at atmospheric pressure with ambient air in order to enhance the polarity of wooden surfaces. One-layer particle boards were produced from the plasma-treated particles by using 3, 5, and 8 % urea formaldehyde adhesive (related to the particles). For all adhesive ratios, internal bond strength was increased by approximately 0.1 MPa co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
2
8
0
3
Order By: Relevance
“…2c, d). This effect of plasma is in accordance with results from previous studies on conventional particleboards (Altgen et al 2015). It was previously reported that mechanical properties of particleboards are enhanced with decreased droplet size (Wilson and Krahmer 1976).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…2c, d). This effect of plasma is in accordance with results from previous studies on conventional particleboards (Altgen et al 2015). It was previously reported that mechanical properties of particleboards are enhanced with decreased droplet size (Wilson and Krahmer 1976).…”
Section: Resultssupporting
confidence: 82%
“…The particles and veneers were treated for 1 s with a rotary cylindrical electrode, using 12.5 Ws/cm 2 and ambient air as process gas as described previously (Altgen et al 2015).…”
Section: Plasma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations have been carrried out on the influence of raw material and production factors on the quality characteristics of particleboards. These factors studied are cutting tool geometry, crushing conditions, particle compaction, fine screen usage, and press closing time (Hızıroglu andGraham 1998, Hızıroglu et al 2004), the use of wood bark and pine cone (Balanchet et al 2000, Ayrılmıs et al 2009, formaldehyde/urea mole ratio, resin level, catalyst level and composition, post treatment and formaldehyde scavengers (Que et al 2007), utilization of bagasse (Ghalehno et al 2011), residue type and tannin content (Moubarik et al 2013), pressing parameters such as times, temperatures, and pressures (Boon et al 2013, Liu et al 2015, the use of plasma treated wood particles (Altgen et al 2015), log position (Muhcu et al 2015), utilization of bamboo and rice husk (Melo et al 2015), utilization of reed stem and canola (Brassica napus) straws (Kord et al 2015, Kord et al 2016, and the use of cotton (Gossypium hirsutum) stalks (Nazerian et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…9 These major effects drive the application of plasma treatments for different goals, such as antifouling properties, 10 biocompatibility, 11 superhydrophobicity, 12 improving surface adhesion, 13,14 oxygen barrier properties 15 and antibacterial properties. 16 The application of plasma in wood and wood-based materials involves two main goals, the improvement of surface adhesion [17][18][19][20][21] and the deposition of low surface energy thin lms to increase the barrier properties against polar and non-polar liquids and gases. The deposition of low surface energy lms on the wood surface is relatively well understood in low-pressure plasma reactors from the many reports published, which mainly use siloxanes, uorine and alkanes as precursors.…”
Section: Introductionmentioning
confidence: 99%